2024
DOI: 10.1021/acs.jafc.3c06442
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial and Antiulcerative Colitis Activities of Essential Oil from Pruni Semen

Ya-Li Wang,
Deng-Qin Lang,
Chao Wu
et al.

Abstract: This study was sought to investigate the chemical composition and antibacterial and antiulcerative colitis (UC) effects of essential oil from Pruni Semen (PSEO). A GC-MS assay showed that the major compounds in PSEO were products of amygdalin hydrolysis, which possessed great antibacterial and anti-inflammatory potential. In vitro antibacterial experiments demonstrated that PSEO treatment inhibited activity of four kinds of intestinal pathogens probably by disrupting the cell wall. Further in vivo studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In the present study, levels of colonic COX-2, iNOS, TNF-α, IL-1β, and IL-6 were markedly elevated in DSS-treated mice compared with those of the control group, while Amy administration markedly lowered the levels of these pro-inflammatory mediators. Surprisingly, a very recent article found that essential oil from Pruni Semen (PSEO), whose main components are products of Amy hydrolysis, had a protective effect against DSS-induced ulcerative colitis in mice, markedly ameliorating the symptoms of colitis, attenuating histopathological damage, and diminishing the production of pro-inflammatory cytokines [ 11 ]. This is consistent with the results of the present study and further supports the anti-colitis effect of Amy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, levels of colonic COX-2, iNOS, TNF-α, IL-1β, and IL-6 were markedly elevated in DSS-treated mice compared with those of the control group, while Amy administration markedly lowered the levels of these pro-inflammatory mediators. Surprisingly, a very recent article found that essential oil from Pruni Semen (PSEO), whose main components are products of Amy hydrolysis, had a protective effect against DSS-induced ulcerative colitis in mice, markedly ameliorating the symptoms of colitis, attenuating histopathological damage, and diminishing the production of pro-inflammatory cytokines [ 11 ]. This is consistent with the results of the present study and further supports the anti-colitis effect of Amy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that Mume Fructus and Prunus mume fruit containing Amy exert protective effects against 2,4,6-trinitrobenzenesulphonic acid (TNBS)-induced colitis in rats [ 10 ]. Moreover, a very recent article showed that essential oil from Pruni Semen (PSEO) has a protective effect against DSS-induced ulcerative colitis in mice and that its active ingredients are mainly products of Amy hydrolysis [ 11 ]. However, the potential role and mechanism of Amy as a monomer in IBD is unknown and deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%